2002
DOI: 10.1128/mcb.22.3.927-934.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Sur7p Family Defines Novel Cortical Domains in Saccharomyces cerevisiae, Affects Sphingolipid Metabolism, and Is Involved in Sporulation

Abstract: We have discovered a novel cortical patch structure in Saccharomyces cerevisiae defined by a family of integral plasma membrane proteins, including Sur7p, Ynl194p, and Ydl222p. Sur7p-family patches localized as cortical patches that were immobile and stable. These patches were polarized to regions of the cell with a mature cell wall; they were absent from small buds and the tips of many medium-sized buds. These patches were distinct from other known cortical structures. Digestion of the cell wall caused Sur7p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
135
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 54 publications
12
135
2
Order By: Relevance
“…The process is reversible, which suggests that the compartment as such is defined by other proteins that are not susceptible to the membrane potential changes. In addition to the H + -symporters above, four proteins of Sur7 family [18,36] and Nce102 with its close homologue Ygr131w [31] were localized in MCC. None of these proteins respond to changes in membrane potential [7,8] and thus, theoretically, they could play the role of those structure-defining elements of MCC.…”
Section: Structure Of MCC Patchesmentioning
confidence: 99%
“…The process is reversible, which suggests that the compartment as such is defined by other proteins that are not susceptible to the membrane potential changes. In addition to the H + -symporters above, four proteins of Sur7 family [18,36] and Nce102 with its close homologue Ygr131w [31] were localized in MCC. None of these proteins respond to changes in membrane potential [7,8] and thus, theoretically, they could play the role of those structure-defining elements of MCC.…”
Section: Structure Of MCC Patchesmentioning
confidence: 99%
“…In both S. cerevisiae and S. pombe, eisosomes are actively excluded from cellular domains where new cell wall is being laid down, such as small buds, growing tips, and mitotic cleavage planes (9,14,43,78,79), suggesting that they may actually interfere with early fungal wall formation but participate in wall maturation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were brought together by Strádalová et al (5), who showed that the membrane compartment occupied by Can1p (MCC) localized to the invaginations seen with freeze fracture EM, and by Karotki et al (6), who showed that Pil1p localizes to the cytoplasmic surfaces of these invaginations. Additional proteins also associate with these punctate domains, in some cases in a transient fashion (17), and the MCC component is reportedly enriched in ergosterol (18) and influenced by phosphoinositide (6,19,20) and sphingolipid (14,17,(21)(22)(23)(24) levels. Hence, the current yeast model (25,26) proposes that Pil1p and Lsp1p, which contain membrane curvatureinducing BAR domains (6,27,28), together with Seg1p (29,30), form a submembrane complex (6) reportedly influenced by Pil1p phosphorylation (25); this complex then either creates or associates with the MCC domains, presumably inducing an inward curvature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, these patches were named MCC, for m embrane c ompartment of C an1, with an appearance of 50 -80 dots per cell and a diameter of approximately 300 nm. These microcompartments also house two other proton-dependent permeases for uracil and tryptophan, Fur4 and Tat2, respectively, as well as four proteins of the Sur7 family (Young et al , 2002 ;Malinska et al , 2004 ). The MCCs are associated with the eisosomes (discussed below) at the inner leaflet of ergosterol-enriched regions of the plasma membrane, which invaginate in furrow-like structures (Grossmann et al , 2008 ;Stradalova et al , 2009 ).…”
Section: Plasma Membrane Compartmentsmentioning
confidence: 99%